Metadiscourse resources across themes of Islamic Friday sermon - Mahmood, Israa Ismaeel; Mohd Kasim, Zalina (UKM Press, 2021)
Friday sermon is a formal speech delivered during the act of worship by the Muslims held before Friday prayer. It is a weekly event that involves disseminating information as well as persuading the congregation through preaching and teaching. In Friday sermons, as a rhetorical religious genre, religious orators usually try to convince an audience using different strategies and language devices such as metadiscourse. Metadiscourse is a rhetorical strategy used to achieve persuasive and communicative purposes as it helps writers (speakers) to engage their audience and guide their understanding of a text. To get insights into how metadiscursive devices contribute to the theme of a sermon, the current study aimed to examine the distribution of rhetorical devices frequency in three themes (belief, practice, and spiritual) of Islamic Friday Sermon (IFS) delivered in English. To achieve the aim of this study, Hyland’s (2005) interpersonal model of metadiscourse was adapted to analyse metadiscourse devices that were deployed in thirty sermons (10 per theme) delivered between 2012 and 2018. The findings reveal the dominant presence of metadiscourse in the sermons of practice/action theme. This indicates the vital role of metadiscourse features in the nature of sermons as a teaching method. Revealing the status of MD rhetorical devises in three different themes can help raise awareness among orators on the appropriate use of MDMs to support the theme of a sermon and make their speeches meaningful, coherent and persuasive.